COVID-19 and Local Emergency Management Operations (American Journal of Management, 2021)
As the COVID-19 pandemic spread across the globe, local (county and municipal) emergency management departments in the United States were thrust to the forefront in addressing the needs of its citizenry. Doing so likely involved the use of Comprehensive Emergency Management (CEM) principles and planning efforts to address the pandemic. This paper outlines how respondents to a May/June 2020 survey of lead local emergency management department professionals nationwide used a variety of tools to address the evolving demands of the pandemic. The results suggest that a majority of local departments report having preparation and response means designed to address a pandemic in place prior to the outbreak of COVID- 19, but the use of specific efforts to confront the virus varied from place to place, as do attitudes regarding the impact of the pandemic on the daily operations of the local emergency management agency.
Keywords: management; COVID-19; coronavirus; emergency management; Federalism; homeland security; pandemic